Time Course for Benefit and Risk of Clopidogrel and Aspirin After Acute Transient Ischemic Attack and Minor Ischemic Stroke: A Secondary Analysis from the POINT Randomized Trial. Issue 8 (20th August 2019) - Johnston, S. Claiborne; Elm, Jordan J.; Easton, J. Donald; Farrant, Mary; Barsan, William G.; Kim, Anthony S.; Lindblad, Anne S.; Palesch, Yuko Y.; Zurita, Karla G.; Albers, Gregory W.; Cucchiara, Brett L.; Kleindorfer, Dawn O.; et al.
Abstract : Background: In patients with acute minor ischemic stroke or high-risk transient ischemic attack enrolled in the POINT trial (Platelet-Oriented Inhibition in New TIA and Minor Ischemic Stroke [POINT] Trial), the combination of clopidogrel and aspirin for 90 days reduced major ischemic events but increased major hemorrhage in comparison to aspirin alone. Methods: In a secondary analysis of POINT (N=4881), we assessed the time course for benefit and risk from the combination of clopidogrel and aspirin. The primary efficacy outcome was a composite of ischemic stroke, myocardial infarction, or ischemic vascular death. The primary safety outcome was major hemorrhage. Risks and benefits were estimated for delayed times of treatment initiation using left-truncated models. Results: Through 90 days, the rate of major ischemic events was initially high then decreased markedly, whereas the rate of major hemorrhage remained low but relatively constant throughout. With the use of a model-based approach, the optimal change point for major ischemic events was 21 days (0–21 days hazard ratio 0.65 for clopidogrel-aspirin versus aspirin; 95% CI, 0.50–0.85; P =0.0015, in comparison to 22–90 days hazard ratio, 1.38; 95% CI, 0.81–2.35; P =0.24). Models showed benefits of clopidogrel-aspirin for treatment delayed as long as 3 days after symptom onset. Conclusions: The benefit of clopidogrel-aspirin occurs predominantly within the first 21 days, and outweighs the low, but ongoing risk of major hemorrhage. When considered with the results of the CHANCE trial (Clopidogrel in High-Risk Patients With Non-disabling Cerebrovascular Events), a similar trial treating with clopidogrel-aspirin for 21 days and showing no increase in major hemorrhage, these results suggest that limiting clopidogrel-aspirin use to 21 days may maximize benefit and reduce risk after high-risk transient ischemic attack or minor ischemic stroke. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00991029.